Investigation of the genic variation in MrkA gene in forming and non-forming biofilm isolates of Klebsiella pneumonia - Al-Khazraji, Shaymaa Fouad Rasheed; Al-Maeni, Mohammad Abdul Rahmman Mohammad; Ahmed, Suaad Ali (Iraqi Journal of Science, 2026)
Biofilm formation is a powerful strategy harbored by Klebsiella pneumonia isolates and helps them prevent antimicrobials from penetrating the cell and escaping the immune system. The aim of the study to correlate the genic variation of MrkA gene in isolates of constructing and non-constructing biofilm. The result showed that 55% of isolates formed biofilm, and their Minimum Bactericidal Concentrations (MBC) were significantly higher than the MBC of non-forming biofilm isolates. In addition, the MBC mediating biofilm destruction was higher than the Minimum Inhibitory Concentration (MIC) mediating planktonic cell killing. This may indicate that the biofilm plays a significant role in the survival of K. pneumonia isolates in their host. Moreover, MrkA gene was only determined in several biofilm-forming isolates, which may indicate their role in forming biofilm. However, studying the genic variation revealed that MrkA gene was conserved, and no variation was detected at all through comparing DNA sequencing of MrkA gene between isolates and the reference genome. Finally, we think MrkA genes participate in biofilm formation, which helps isolates persist for a long time in their host.